Participatory Impact Pathways Analysis: A practical method for project planning and evaluation - Douthwaite, Boru; Álvarez, S.; Thiele, Graham; Mackay, R. (2008)
Participatory Impact Pathways Analysis (PIPA) is a practical planning, and monitoring and evaluation approach developed for use with complex projects in the water and food sectors . PIPA begins with a participatory workshop where stakeholders make explicit their assumptions about how their project will achieve an impact. Participants construct problem trees, carry out a visioning exercise and draw network maps to help them clarify their 'impact pathways'. These are then articulated in two logic models. The outcomes logic model describes the project's medium term objectives in the form of hypotheses: which actors need to change, what are those changes and which strategies are needed to realise these changes. The impact logic model describes how, by helping to achieve the expected outcomes, the project will impact on people's livelihoods. Participants derive outcome targets and milestones which are regularly revisited and revised as part of project monitoring and evaluation (M&E). PIPA goes beyond the traditional use of logic models and logframes by engaging stakeholders in a structured participatory process, promoting learning and providing a framework for 'action research' on processes of change.